Spotlighting climate, gender, and peace at Zimbabwe's 2nd climate change and development conference - Ndlovu, Sindiso; Maviza, Gracsious; Takaindisa, Joyce (2024)
At the 2nd Climate Change and Development Conference in Zimbabwe, the CGIAR FOCUS Climate Security Team led two panels, one on climate, gender, and inclusivity and another on climate, peace, and security in Zimbabwe. This conference, co–organised by the Ministry of Environment, Climate, and Wildlife, the University of Zimbabwe’s Environment, Climate, and Sustainable Development Institute, NDC Partnership, the International Centre for Tropical Agriculture (CIAT), UNDP, UNICEF, and Africa Carbon Markets Forum (ACMF) was an iteration of the successful inaugural Climate Change and Development Conference in 2023. The conference aimed to help Zimbabwe craft a sustainable path to socioeconomic development in the face of climate change and its adverse effects.